2008
DOI: 10.1111/j.1365-2869.2008.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and affect in older adults: using multilevel modeling to examine daily associations

Abstract: SUMMARYThe main objective of the present study was to examine daily associations (intraindividual variability or IIV) between sleep and affect in older adults. Greater understanding of these associations is important, because both sleep and affect represent modifiable behaviors that can have a major influence on older adults' health and well-being. We collected sleep diaries, actigraphy, and affect data concurrently for 14 days in 103 community-dwelling older adults. Multilevel modeling was used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
150
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 63 publications
18
150
2
Order By: Relevance
“…In terms of the relationships between sleep quality, affects, and LS, the findings were consistent with those of the literature: Better sleep quality was associated with less NA (Bower et al, 2010;Huang et al, 2016), more PA (Bower et al, 2010;Mccrae et al, 2008), and greater LS (Paunio et al, 2009). These findings can probably be explained by the experimentally observed link between sleep loss and mood regulation deficits (Yoo et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of the relationships between sleep quality, affects, and LS, the findings were consistent with those of the literature: Better sleep quality was associated with less NA (Bower et al, 2010;Huang et al, 2016), more PA (Bower et al, 2010;Mccrae et al, 2008), and greater LS (Paunio et al, 2009). These findings can probably be explained by the experimentally observed link between sleep loss and mood regulation deficits (Yoo et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Greater daytime dysfunction and lower subjective sleep quality are associated with lower levels of PA and higher levels of NA (Bower et al, 2010;Mccrae et al, 2008). Longitudinally, sleep quality positively predicts LS (Paunio et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Mood regulation is a potential mediator of the exercise-sleep relationship in older adults. The exercise-related effects on depression and anxiety may mediate the benefits of physical activity on sleep behavior (Mccrae et al, 2008;Bonnet and Arand, 1995). Aerobic exercise improves sleep efficiency and reduces depressive symptoms in older adults with insomnia .…”
Section: Sleep As a Possible Mediator For Some Of The Effects Of Physmentioning
confidence: 99%
“…Interestingly, among older adults with insomnia, about 40% have possible anxiety difficulties [10]. Supporting these comorbidity estimates, cross-sectional [11] and prospective studies [12] have found that higher levels of the components of anxiety are correlated with greater sleep difficulties among older adults.…”
Section: Introductionmentioning
confidence: 94%